Kajian ekonometrik industri minyak kelapa sawit di Sabah - Remali Yusoff (Universiti Malaysia Sabah, 2007)
The objective of the study is to determine the factors influencing the supply and demand for Sabah palm oil industry. A structural model of the Sabah palm oil industry is estimated using annual data for the 1970-1996 period.. The structural moJd consists of four behavioural equations and one identity. A block recursive functional form is used and estimated using the two-stage least squares in the log linear form. The behavioural equations are used to estimate influences of various factors on the hectarage of mature oil palm, the production of oil palm, the domestic demand and the foreign demand for Sabah palm oil. The estimation results showed that the matured area is influenced by the domestic price of the oil pal~ local prices of dried cocoa beans, costs of labour and interest rates. The important factors are domestic prices of the oil palm, costs of labour and interest rate. The production influenced by the matured area, the quantity of labour, quantity of fertilizers used and level of technology. The important factors are matured area, quantity of fertilizers used and level of technology. The domestic demand influenced by the domestic prices of oil palm, price of copra, average price of soap, Sabah GNP, total population and local demand in the previous year. The important factors are domestic prices of oil palm, average price of soap, Sabah GNP, total population and local demand in the previous year. It is also shown that among thr factors influencing the foreign demand for Sabah oil palm industry include the domestic demand of oil palm, price of soya beans, world oil palm consumption, the exchange rate of Malaysia Ringgit relative to US dollar and one year lag foreign demand. The important factors are domestic demand of oil pal~ world oil palm consumption, the exchange rate" of Malaysia Ringgit relative to US dollar "and one year lag foreign demand. The implications the study is that by lowering the interest rate for loan or fixing the interest rate at an appropriate level, increasing production" by enhancing labour productivity and using 1Jptimum fertilizer, increasing the local processing and manufacturing of oil palm sector, are important for enhancing the development of Sabab's oil palm industry. In addition, model assessment is made to evaluate the compatibility of the said model between the estimated and actual values.